PENGARUH BERMAIN PROYEK KOLABORATIF DENGAN MEDIA PLASTISIN TERHADAP KREATIVITAS ANAK USIA DINI DI RA AL IKHLAS KABUPATEN TAKALAR - Nur Afdelia; Parwoto; Hajerah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of collaborative project-based play using plasticine media on the creativity of early childhood aged 5–6 years at RA Al Ikhlas, Takalar Regency. This study used a quantitative approach with a quasi-experimental research design in the form of a pretest-posttest control group design. The population consisted of all Group B children at RA Al Ikhlas, Takalar Regency, with a sample of 20 children selected through purposive sampling, consisting of 10 children in the experimental group and 10 children in the control group. Data were collected through structured observation of four creativity indicators (fluency, flexibility, originality, and elaboration) and analyzed using descriptive statistics and parametric statistics (normality test, homogeneity test, Paired Sample t-Test, and Independent Sample t-Test) with the assistance of SPSS version 22. The results showed that the mean pretest score of the experimental group increased from 15.60 to 27.50 at posttest, while the mean score of the control group increased only from 15.40 to 16.40. The Paired Sample t-Test showed a significance value of 0.000 < 0.05 for both groups, while the Independent Sample t-Test on the posttest scores yielded t = 20.601 and a significance value of 0.000 < 0.05, indicating a statistically significant difference between the experimental and control groups. It can therefore be concluded that collaborative project-based play using plasticine media has a significant positive effect on the creativity of early childhood at RA Al Ikhlas, Takalar Regency. Keywords: Early Childhood Creativity, Collaborative Project-Based Play, Plasticine Media.